Selected eHealth Applications in Cyprus from the Training Perspective - Jossif, A.; Pattichis, C.S.; Kyriakides, M.; Pitsillides, A.; Kyriacou, E.; Dikaiakos, M. (Methods of Information in Medicine, 2007)
Objectives: In this paper a review of selected eHealth applications in Cyprus is presented linked with their success or failure based on their training activities.Methods: The eHealth systems presented and their training activities include an update of the health information system (HIS) in the public hospitals, a medical system for emergency telemedicine (AMBULANCE and EMERGENCY-112 projects), a home monitoring system for cancer patients (DITIS), a satellite-based network in healthcare applications (EMISPHER and HEALTHWARE projects), and the training activities of the Cyprus Society of Medical Informatics. Different methodologies for training were used ranging from classical approaches like train the trainers, using demo cases followed by personal training, group training, and workshops, to more recent methodologies based on eLearning sessions including teleconsultations.Results: The training was carried out successfully in all cases. However, not all eHealth systems were put into practice successfully, mainly for reasons not related to training.Conclusions: It is anticipated that this paper will promote the importance of these applications and their training activities as well as help in the spin off of others thus enabling the offering of a better service to the citizen.
Keywords: eHealth; health telematics; medical informatics; eLearning; training